2018
DOI: 10.1016/j.ibror.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in the olfactory bulb and olfactory deficits in the Ccdc66 -/- mouse model for retinal degeneration

Abstract: HighlightsCCDC66 protein is expressed throughout the early postnatal development in the WT mouse brain.CCDC66 protein expression levels in the olfactory bulb are comparable to the retina in adult (3-month-old) WT mice.The Ccdc66-deficient retinal degeneration mouse model also exhibits impairment of the olfactory system.Severe degeneration was detected in olfactory bulb glomeruli of adult Ccdc66 -/- mice.Ccdc66-deficient mice show alteration of olfaction-related behavior at advanced age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Curiously, CCDC66 may impact smell as well as vision. CCDC66 −/− mice also display neurodegeneration of the olfactory bulb, and have reduced odor discrimination performance of lemon smells ( 72 ). The ecological significance of this result, if any, is unclear at present but may warrant future attention.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, CCDC66 may impact smell as well as vision. CCDC66 −/− mice also display neurodegeneration of the olfactory bulb, and have reduced odor discrimination performance of lemon smells ( 72 ). The ecological significance of this result, if any, is unclear at present but may warrant future attention.…”
Section: Discussionmentioning
confidence: 99%
“…ERG in these mice pointed to primary rod degeneration accompanied, to a lesser extent, by cone degeneration, following a time course comparable to RP in humans rather than other more rapidly progressive RP mouse models. In a more recent study, a substantial olfactory nerve fiber degeneration and alteration of olfaction-related behavior was described in aged Ccdc66−/− mice 47 . As both photoreceptors and olfactory sensory neurons that undergo degeneration are ciliated, Ccdc66 −/− mice appear to represent a ciliopathy-like disease.…”
Section: Discussionmentioning
confidence: 92%
“…CCDC66 has been implicated in several developmental disorders including retinal degeneration and Joubert syndrome (Dekomien et al, 2010; Gerding et al, 2011; Latour et al, 2020; Murgiano et al, 2020; Schreiber et al, 2018). Consistent with its link to ciliopathies, we and others previously showed that retinal degeneration mutations disrupt its ciliary functions and interactions (Conkar et al, 2017; Murgiano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We previously characterized coiled coil protein 66 (CCDC66) as a MAP and a regulator of primary cilium formation and composition in quiescent cells(Conkar et al, 2019; Conkar et al, 2017). It was originally described as a gene mutated in retinal degeneration and later characterized for its retinal and olfactory functions using CCDC66 -/- mouse (Dekomien et al, 2010; Gerding et al, 2011; Murgiano et al, 2020; Schreiber et al, 2018). Recently, CCDC66 was identified as part of the Joubert syndrome interaction network consisting of other MAPs such as CSPP1, TOGARAM1 and CEP290 (Latour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%